(untitled) (Italian Journal of Public Health, 2005)
Over the past decade there has been a steady increase in the number of malpractice claims brought against healthcare providers [1,2] and in the monetary damages awarded to plaintiffs [1,3]. This increase has precipitated numerous state programs designed to moderate the number of claims and encourage providers to develop quality of care initiatives [4,5]. It is important to develop more reliable estimates of the incidence of adverse events and negligence in hospitalized patients.An adverse event is defined as an injury caused by medical management (rather than the underlying disease) that prolongs the hospitalization and results in disability at the time of discharge, or both. Negligence is defined as care that has fallen below the standard expected of physicians in their community. The Harvard Medical Practice Study (HMPS) was first published in 1991 and was based on 1984 case records of more than 30,000 randomly selected records from 51 randomly selected acute care, nonpsychiatric hospitals.The study attempts to measure the extent of medical malpractice in hospitals in the state of New York, and compare the resulting patterns with the negligence claims actually filed [6-8]. The HMPS reviews randomly selected records with disability injuries caused by medical treatment.To establish that an adverse event or negligence has occurred, it uses as a criterion an average confidence score of four or more (on a six point scale). Data identified are age, sex, and primary discharge diagnosis. The significance of the differences in rates of adverse events and negligence according to sex and age were tested.